Tidal phasing drives intertidal heat stress and climate vulnerability - Sophie‐Berenice Wilmes; Luis Giménez; Stuart R. Jenkins; Emily Perks; Ben Winterbourn; Shelagh K. Malham; Peter E. Robins (Limnology and Oceanography, 2026)
Intertidal organisms are exposed to extreme and variable thermal conditions due to periodic aerial exposure by tides. For sessile species that cannot seek refuge, heat stress is strongly influenced by the timing of low tides, which in semidiurnal tidal systems is governed by the spring–neap tidal cycle. Here, we deployed biomimetic loggers, designed to replicate body temperature of the mussel Mytilus edulis , at two climatologically similar yet tidally distinct sites in Wales, UK, to examine how interactions between climate and tidal phasing regulate intertidal heat stress. Despite comparable weather conditions, South Wales mussels—exposed during midday spring low tides—experienced daily maximum body temperatures over 3°C higher compared to North Wales, where exposure occurred during morning and evening spring low tides. Consequently, South Wales mussels exceed critical temperature thresholds more frequently. Based on the observations, we developed and validated a mussel body temperature model incorporating readily available tidal and climatic data, which accurately reproduced observed logger temperatures and successfully simulated a 2018 mass mortality event in the English Channel. Model experiments showed that tidal phasing can modulate 95 th ‐percentile daily maxima by up to 5.5°C, with midday spring low tides producing the warmest possible conditions. Long‐term simulations (1990–2023) further revealed a 2 to 2.5‐fold increase in extreme temperature exposure since 2020. These results demonstrate that tidal characteristics in semidiurnal systems can amplify or mitigate intertidal thermal stress as strongly as local climate, and that simple, process‐based models can forecast heat exposure and ecological vulnerability under future climate change.

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Estimating the trapping area and density of common whelk (Buccinum undatum) using experimental fishing - Matthew J. Garratt; Isobel S.M. Bloor; Matthew T. Coleman; Charlotte N. Colvin; Jan Geert Hiddink; Natalie Hold; Stuart R. Jenkins (Fisheries Research, 2025)

Establishing the role of the North Atlantic Oscillation as a potential driver of brown crab Cancer pagurus density - Matthew T. Coleman; Isobel S.M. Bloor; Stuart R. Jenkins (Fisheries Research, 2024)

Environmental factors have stronger effects than biotic processes in patterns of intertidal populations along the southeast coast of Brazil - Cesar A.M.M. Cordeiro; André Pardal; Luis Giménez; Áurea M. Ciotti; Stuart R. Jenkins; Michael T. Burrows; Gray A. Williams; Ronaldo A. Christofoletti (Marine Environmental Research, 2024)

Habitat structure shapes temperate reef assemblages across regional environmental gradients - Tim Jackson-Bué; Ally J. Evans; Peter J. Lawrence; Paul R. Brooks; Sophie L. Ward; Stuart R. Jenkins; Pippa J. Moore; Tasman P. Crowe; Simon P. Neill; Andrew J. Davies (Science of The Total Environment, 2024)

Local and large-scale spatial variation in a marine predator–prey interaction in the southwestern Atlantic - André Pardal; Stuart R. Jenkins; Ronaldo A. Christofoletti (Oecologia, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The use of environmental DNA metabarcoding and quantitative PCR for molecular detection of marine invasive non-native species associated with artificial structures - Laura M. Gargan; Paul R. Brooks; Siobhan R. Vye; Joseph E. Ironside; Stuart R. Jenkins; Tasman P. Crowe; Jens Carlsson (Biological Invasions, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Participatory Monitoring—A Citizen Science Approach for Coastal Environments - Paula Kasten; Stuart R. Jenkins; Ronaldo A. Christofoletti (Frontiers in Marine Science, 2021)
In this article the authors share their experiences, results, and lessons learned during the creation of a coastal biodiversity participatory monitoring initiative. Throughout 2019, we delivered five training workshops to 51 citizen scientists. Data collected by the citizens scientists were validated by checking its similarities against that gathered by specialists. High similarity values were found, indicating that, if proper training is provided, there is a great potential for citizen scientists to contribute biodiversity data with high value. During this process a certain level of variation in data produced by specialists was found, drawing attention to the need for prior alignment among specialists who may offer training for citizens. In addition, despite overall similar results between specialists and participants, some differences emerged in particular parts of the habitat; for example, the bivalve zones presented higher complexity and hence greater challenge. Identifying key challenges for participants is key to developing appropriate citizen science protocols. Here it is provided preliminary evidence that supports the use of the monitoring protocol to obtain biodiversity data gathered by citizen scientists, assuring its scientific quality. Enhancing participation by the community and specialists is key to further validate the approach and to effectively expand such protocols, enhancing the level of biodiversity data collection. In order to promote participation, and maintain citizen scientist engagement in the initiative, it is recommended the development of new investigations that assess the interests and motivations of the public to take part. It is also fundamentally important to have an effective strategy to communicate the results of participants’ monitoring and their applicability to local and global issues, thus maximizing the continuity of engagement of citizen scientists.

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

Novel co‐occurrence of functionally redundant consumers induced by range expansion alters community structure - Moisés A. Aguilera; Nelson Valdivia; Bernardo R. Broitman; Stuart R. Jenkins; Sergio A. Navarrete (Ecology, 2020)
Ongoing climate change is shifting the geographic distributions of some species, potentially imposing rapid changes in local community structure and ecosystem functioning. Besides changes in population‐level interspecific interactions, such range shifts may also cause changes in functional structure within the host assemblages, which can result in losses or gains in ecosystem functions. Because consumer‐resource dynamics are central to community regulation, functional reorganization driven by introduction of new consumer species can have large consequences on ecosystem functions. Here we experimentally examine the extent to which the recent poleward range expansion of the intertidal grazer limpet Scurria viridula along the coast of Chile has altered the role of the resident congeneric limpet S. zebrina, and whether the net collective impacts, and functional structure, of the entire herbivore guild have been modified by the introduction of this new member. We examined the functional role of Scurria species in controlling ephemeral algal cover, bare rock availability, and species richness and diversity, and compared the effects in the region of range overlap against their respective “native” abutted ranges. Experiments showed depression of per capita effects of the range‐expanded species within the region of overlap, suggesting environmental conditions negatively affect individual performance. In contrast, effects of S. zebrina were commonly invariant at its range edge. When comparing single species versus polycultures, effects on bare rock cover were altered by the presence of the other Scurria species, suggesting competition between Scurria species. Importantly, although the magnitude of S. viridula effects at the range overlap was reduced, its addition to the herbivore guild seems to complement and intensify the role of the guild in reducing green algal cover, species richness and increasing bare space provision. Our study thus highlights that range expansion of an herbivore can modify the functional guild structure in the recipient community. It also highlights the complexity of predicting how functional structure may change in the face of natural or human‐induced range expansions. There is a need for more field‐based examination of regional functional compensation, complementarity, or inhibition before we can construct a conceptual framework to anticipate the consequences of species range expansions.

Role of trait combinations, habitat matrix, and network topology in metapopulation recovery from regional extinction - Luis Giménez; Peter Robins; Stuart R. Jenkins (Limnology and Oceanography, 2020)
We studied the role of oceanographic conditions and life history strategies on recovery after extinction in a metapopulation of marine organisms dispersing as pelagic larvae. We combined an age‐structured model with scenarios defined by realistic oceanographic conditions and species distribution along the Irish Sea coast (North Europe). Species life history strategies were modeled combining the dispersal behaviors with two levels of fecundity. Recovery times were quantified after simulating extinction in four regions. Two alternative strategies (high fecundity or larval tidal transport) led to short recovery times, irrespective of the effects of other drivers. Other strategies and low larval survival exacerbated the effects of oceanographic conditions on recovery times: longer times were associated with for example the presence of frontal zones isolating regions of extinction. Recovery times were well explained by the connectivity of each focal population with those located outside the area of extinction (which was higher in the so‐called small world topologies), but not by subsidies (direct connections with populations located nearby). Our work highlights the complexities involved in population recovery: specific trait combinations may blur the effects of the habitat matrix on recovery times; K‐strategists (i.e., with low fecundities) may achieve quick recovery if they possess the appropriate dispersal traits. High larval mortality can exacerbate the effect of oceanographic conditions and lead to heterogeneity in recovery times. Overall, processes driving whole network topologies rather than conditions surrounding local populations are the key to understand patterns of recovery.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Opposing Indirect Effects of Domestic Herbivores on Saltmarsh Erosion - Jordi F. Pagès; Stuart R. Jenkins; Tjeerd J. Bouma; Elwyn Sharps; Martin W. Skov (Ecosystems, 2019)

Evidence for enhanced late-stage larval quality, not survival, through maternal carry-over effects in a space monopolizing barnacle - Paula Kasten; Stuart R. Jenkins; Réjean Tremblay; Augusto A. V. Flores (Hydrobiologia, 2019)

Incorporating social dimensions in planning, managing and evaluating environmental projects - C. Louise Goggin; Thomas Barrett; John Leys; Gregory Summerell; Emma Gorrod; Stuart Waters; Mark Littleboy; Tony D. Auld; Michael J. Drielsma; Brian R. Jenkins (Environmental Management, 2019)

Successional convergence in experimentally disturbed intertidal communities - Gustavo M. Martins; Francisco Arenas; Fernando Tuya; Rubén Ramírez; Ana I. Neto; Stuart R. Jenkins (Oecologia, 2018)

Evaluating the relative conservation value of fully and partially protected marine areas - Marija Sciberras; Stuart R Jenkins; Rebecca Mant; Michel J Kaiser; Stephen J Hawkins; Andrew S Pullin (Fish and Fisheries, 2015)
The establishment of marine protected areas ( MPA s), particularly of no‐take areas, is often viewed as a conflict between conservation and fishing. Partially protected areas ( PPA s) that restrict some extractive uses are often regarded as a balance between biodiversity conservation and socio‐economic viability. Few attempts have been made to generalize the ecological effects of PPA s. We synthesized the results of empirical studies that compared PPA s to (i) no‐take reserves ( NTR s) and (ii) to open access ( O pen) areas, to assess the potential benefits of different levels of protection for fish populations. Response to protection was examined in relation to MPA parameters and the exploitation status of fish. Our syntheses suggest that while PPA s significantly enhance density and biomass of fish relative to O pen areas, NTR s yielded significantly higher biomass of fish within their boundaries relative to PPA s. The positive response to protection was primarily driven by target species. There was a large degree of variability in the magnitude of response to protection, although the size of the PPA explained some of this variability. The protection regime within the PPA provided useful insights into the effectiveness of partial MPA s. We conclude that MPA s with partial protection confer advantages, such as enhanced density and biomass of fish, compared to areas with no restrictions, although the strongest responses occurred for areas with total exclusion. Thus, MPA s with a combination of protection levels are a valuable spatial management tool particularly in areas where exclusion of all activities is not a socio‐economically and politically viable option.

Phenotypic variation in shell form in the intertidal acorn barnacle Chthamalus montagui: distribution, response to predators and life history trade-offs - Jefferson Murua; Michael T. Burrows; Roger N. Hughes; Stephen J. Hawkins; Richard C. Thompson; Stuart R. Jenkins (Marine Biology, 2014)

Linking temperate demersal fish species to habitat: scales, patterns and future directions - Andrew F Johnson; Stuart R Jenkins; Jan G Hiddink; Hilmar Hinz (Fish and Fisheries, 2013)
Adoption of the ecosystem approach to fisheries management relies on recognition of the link between fish and other components of the ecosystem, namely their physical and biological habitat. However, identifying the habitat requirements of marine fishes and hence determining their distribution in space and time is scientifically complex. We analysed the methodologies and findings of research on temperate, demersal fish habitat requirements to highlight the main developments in this field and to identify potential shortfalls. Many studies were undertaken over large spatial scales (≥100s km 2 ) and these generally correlated abundances of fish to abiotic variables. Biological variables were accounted for less often. Small spatial scale (≤m 2 ), experimental studies were comparatively sparse and commonly focused on biotic variables. Whilst the number of studies focusing on abiotic variables increased with increasing spatial scale, the proportion of studies finding significant relationships between habitat and fish distribution remained constant. This mismatch indicates there is no justification for the tendency to analyse abiotic habitat variables at large spatial scales. Innovative modelling techniques and habitat mapping technologies are developing rapidly, providing new insights at the larger spatial scales. However, there is a clear need for a reduction in study scale, or increase in resolution additional to the integration of biotic variables. We argue that development of sound predictive science in the field of demersal fish habitat determination is reliant on a change in focus along these lines. This is especially important if spatial management strategies, such as Marine Protected Areas (MPA) or No Take Zones (NTZ), are to be used in future ecosystem‐based approaches to fisheries management.

Physical and biological controls on larval dispersal and connectivity in a highly energetic shelf sea - Peter E. Robins; Simon P. Neill; Luis Giménez; Stuart R. Jenkins; Shelagh K. Malham (Limnology and Oceanography, 2013)
Connectivity within marine species plays a fundamental role in population dynamics, genetic diversity, spread of disease, and resilience to human exploitation. However, for shellfish species that are sessile as adults, the larval‐dispersal stage remains largely unresolved. Appreciation of larval connectivity is therefore crucial to population genetics and marine management. We describe a coupled three‐dimensional hydrodynamic and Lagrangian particle tracking model used to simulate larval transport and show how temporal and spatial hydrodynamic changes, together with larval behavior, are likely to affect dispersal. A case study of Irish Sea (United Kingdom) shellfish populations incorporates a wide range of hydrodynamic environments that are prevalent in other marine systems around the world. Our simulations tested two main processes that control larval dispersal: hydrodynamics and vertical migration. Simulated larval cohorts were released from estuaries and soft sediment locations in regions that were oceanographically distinct. Larvae originating from exposed areas could migrate offshore (low retention and high connectivity) and disperse farther than larvae that remained in flood‐dominant estuaries, which promote retention. Simulated self‐recruitment and connectivity with neighboring populations (∼ 50 km apart) were generally high, although well‐developed mesoscale residual currents were important, controlling dispersal pathways offshore. Vertical migration strategies, synchronized either with the tide (tidal stream transport) or with the Earth's rotation (diel transport), enabled more larvae to remain close to the coast, and simulations indicated higher retention than for passive larvae. However, the probability of connectivity with other populations and potential survivorship was greater for tidal strategies than for passive (although passive transport populated more distinct areas albeit in smaller proportions, as more larvae remained stranded offshore), or diel, where larvae remained close to their release location.

Determinants of reproductive potential and population size in open populations of Patella vulgata - Andreas Sundelöf; Stuart R. Jenkins; Carl J. Svensson; Jane Delany; Stephen J. Hawkins; Per Åberg (Marine Biology, 2010)

COMPARATIVE ECOLOGY OF NORTH ATLANTIC SHORES: DO DIFFERENCES IN PLAYERS MATTER FOR PROCESS? - Stuart R. Jenkins; Pippa Moore; Michael T. Burrows; David J. Garbary; Stephen J. Hawkins; Agnar Ingólfsson; Kenneth P. Sebens; Paul V. R. Snelgrove; David S. Wethey; Sarah A. Woodin (Ecology, 2008)
The contrasting histories of the western and eastern shores of the North Atlantic Ocean provide an excellent opportunity to consider the implications of past events for present ecological processes and the functioning of marine ecosystems. Similarities and differences in assemblage composition have been driven by large‐scale events, such as the trans‐Arctic interchange, which has shaped the species pool, and cycles of glaciation, which have determined phases of local or regional extinction and colonization. More recently, anthropogenically induced invasions and local extinctions have significantly altered biogeographic distributions. Here we consider for both hard and soft substrata how the presence or absence of key taxa influences the outcomes of trophic and other biological interactions, and evaluate the consequences for community structure and ecosystem functioning. On intertidal hard substratum shores, biodiversity of epilithic microphagous grazers differs across latitudinal and longitudinal scales. Diversity is high in southern Europe but declines to the north and across the Atlantic. Lower diversity and the absence of patellid limpets in Iceland and the northwest Atlantic compared to Europe result in differences in consumer pressure, and an apparent contrast in the importance of herbivory vs. competitive interactions and predation pressure as community structuring processes. Interestingly, despite differences in “process,” community patterns are remarkably similar between the east and west. On soft sediment shores, there are conspicuous geographic differences in importance of bioturbators and large digging predators. Hemichordates can be abundant and important infaunal bioturbators in the western Atlantic, but they generally play a much reduced role in the eastern Atlantic. In addition, the number and diversity of digging predators on western Atlantic shores is high; the horseshoe crab, swimming portunid crabs, large whelks, excavating waterfowl, and an abundance of skates and rays exert intense predation pressure and associated biogenic disturbance to sediments. In Europe, except for excavating waterfowl these taxa are rare or absent. Thus, the importance of large, biological agents of disturbance is lower on European shores as a consequence of both recent anthropogenic pressure and natural processes over larger time scales. Consideration of key structuring taxa over the Atlantic shows that human‐mediated transport has had considerable influence. Faunas on both sides of the Atlantic are becoming more similar to the point that some of the key differences in assemblage composition and hence community organization have blurred. Recent introductions as well as planned experimental manipulations provide the opportunity to understand the role of species identity in determining community structure and ecosystem functioning over large spatial scales; the North Atlantic may be an ideal test system to explore these areas.

A continental scale evaluation of the role of limpet grazing on rocky shores - Ross A. Coleman; Antony J. Underwood; Lisandro Benedetti-Cecchi; Per Åberg; Francisco Arenas; Julio Arrontes; João Castro; Richard G. Hartnoll; Stuart R. Jenkins; José Paula; Paolo Della Santina; Stephen J. Hawkins (Oecologia, 2006)

Population resistance to climate change: modelling the effects of low recruitment in open populations - Carl Johan Svensson; Stuart R. Jenkins; Stephen J. Hawkins; Per berg (Oecologia, 2005)